Investments - Sharpe, William F.; Alexander, Gordon J.; Bailey, Jeffery V. (Upper Saddle River, N.J. : Prentice Hall, 2000)
"The subject matter for this edition of Investments has evolved considerably since 1978 when the first edition was published. For example, in the last several years international investing has expanded rapidly, securities such as swaps and mortgage derivatives have become increasingly popular, and investors have placed much more emphasis on investment styles.
The task of the authors has been to keep Investments fresh and stimulating and to continue the tradition of this text to offer students and instructors the most thorough and most current survey of the investment environment."--BOOK JACKET.
Keywords: Investments; Investment analysis; Investments